ANALISIS HUBUNGAN KEKERINGAN METEOROLOGIS DENGAN KEKERINGAN AGRIKULTURAL DI PULAU LOMBOK MENGGUNAKAN KORELASI PEARSON - Dzikrullah Akbar; Siti Najma Nindya Utami; Rista Hernandi Virgianto (Delta: Jurnal Ilmiah Pendidikan Matematika, 2021)
One of the disasters can cause losses in various sectors and have an impact on people's lives is drought. Lombok Island is an area with a high risk of drought. The Standardized Precipitation Index (SPI) describes meteorological drought using rainfall as the main parameter. The Normalized Differences Vegetation Index (NDVI) describes agricultural drought based on remote sensing. This research aims to determine the relationship between SPI using the reanalysis rainfall data Climate Hazards Group InfraRed Precipitation with Stations (CHIRPS) with observed rainfall (CH Obs) and NDVI at 22 rain observation stations on Lombok Island during the 2001 – 2018. The use method is to calculate the Pearson correlation and the significance of SPI with CH Obs and NDVI. The correlation between SPI with CH Obs and NDVI is positive and significant, respectively 0.31 and 0.21 with p-value <0.05. This illustrates that drought monitoring using reanalysis and remote sensing data can be done because it describes the actual drought in the study area. In addition, it can be concluded that the meteorological drought that occurred could have an impact on agricultural drought in the Lombok during 2001 - 2018.